A methodology to quantify the uncertainty in liquid holdup measurements with wire mesh sensor. (December 2015) - Vuong, Duc H.; Aydin, Tayfun Besim; Torres, Carlos F.; Schleicher, Eckhard; Pereyra, Eduardo; Sarica, Cem
Abstract: The uncertainty in the holdup measurements of a capacitance based WMS with 32×32 wires has been experimentally evaluated, and a methodology for its quantification is proposed for horizontal flow. Investigation is performed in laboratory and in-situ experiments under stagnant conditions with an emphasis on the effect of the mesh grid orientation on the measurements. Also, potential impact of misalignment in the pipe inclination is explored by slightly inclining the pipe for both tests. Finally, dynamic flow conditions are tested in a high pressure (1.37 MPa) facility with horizontal stratified-wavy oil/air two-phase flow for gas and liquid superficial velocity ranges of 2.8 m/s≤ ν Sg ≤6.9 m/s and 0.01 m/s≤ v SL ≤0.05 m/s, respectively. The angle between the phase interface and the sensor wires is ineffective while the misalignment in the pipe inclination plays a major role in the deviations of the holdup measurements. Using the proposed methodology, the measurement uncertainty from laboratory tests is shown to follow a logarithmic increase as a function of the measured holdup for smaller holdup values ( H L ≤15%) and to be lower than 1.5% for H L >15%. This behavior is intrinsic to WMS and a representative of the measurement uncertainty in the actual flow loop installation. Under actual flow conditions, the holdup measurements of the trapped liquid by WMS show an offset compared to the measurements via flow imaging which can be corrected by using the uncertainty quantified in the laboratory tests. However, the dynamic measurements with WMS show a good agreement with the holdup of the trapped liquid volume within the quantified uncertainty bounds. Highlights: The uncertainty in liquid holdup measurements of Wire Mesh Sensors is evaluated. A methodology is proposed for the quantification of measurement uncertainty. Uncertainty in laboratory tests represent in-situ conditions. For holdup values up to 15%, uncertainty increases logarithmically to 1.5%. For holdup values larger than 15%, the uncertainty is limited to 1.5%.